BR 46 Adsorption Application: In Situ HF Production of Ti3C2Tx via LiF/HCl Etching - Çelik, Aytekin; Halisdemir, Umay; Köse, Yusuf; Yegin, Mustafa (My University, 2024)
This study investigates the adsorption capabilities of Ti3C2Tx MXene to remove Basic Red 46 (BR 46) dye from aqueous solutions. Azo dyes such as BR 46 are common pollutants from textile industries and pose significant ecological and health risks due to their toxicity and persistence. Current removal methods face efficiency issues af-fected by dye composition, pH, and other contaminants. Advanced oxidation pro-cesses (AOPs) and adsorption methods are promising but require optimization for practical application. MXenes, two-dimensional transition metal carbides/nitrides, offer high adsorption capacity and stability. In this study, the titanium aluminum carbide (Ti3AlC2) MAX phase was exfoliated using lithium fluoride (LiF)+hydrochloride acid (HCl) to synthesize Ti3C2Tx. Characterization techniques including Fourier transform infrared spectrometry (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM) were used to analyze the material. The study examined the effects of various reaction conditions such as pH, MXene dosage, and initial dye concentration on BR 46 adsorption. The results show that Ti3C2Tx MXene is an effective adsorbent and provides a potential solution for removing toxic dyes from wastewater. This study contributes to developing efficient, cost-effective, and sus-tainable methods to reduce dye pollution in water resources.
Keywords: Adsorption; Azo dye; MXene; LiF/HCl